An FPGA Task Placement Algorithm Using Reflected Binary Gray Space Filling Curve - Senoj Joseph Olakkenghil; K. Baskaran (International Journal of Reconfigurable Computing)
With the arrival of partial reconfiguration technology, modern FPGAs support tasks that can be loaded in (removed from) the FPGA individually without interrupting other tasks already running on the same FPGA. Many online task placement algorithms designed for such partially reconfigurable systems have been proposed to provide efficient and fast task placement. A new approach for online placement of modules on reconfigurable devices, by managing the free space using a run-length based representation. This representation allows the algorithm to insert or delete tasks quickly and also to calculate the fragmentation easily. In the proposed FPGA model, the CLBs are numbered according to reflected binary gray space filling curve model. The search algorithm will quickly identify a placement for the incoming task based on first fit mode or a fragmentation aware best fit mode. Simulation experiments indicate that the proposed techniques result in a low ratio of task rejection and high FPGA utilization compared to existing techniques.